1977
DOI: 10.1017/s0043174500033397
|View full text |Cite
|
Sign up to set email alerts
|

Soil Degradation of Three Dinitroanilines

Abstract: These studies were conducted in the laboratory on two soils at two temperatures to define the rate of degradation and the associated rate law for trifluralin (α,α,α-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine), benefin (N-butyl-N-ethyl-α,α,α-trifluoro-2,6-dinitro-p-toluidine), and 2,6-dinitro-N-(3-pentyl)-α,α,α-trifluoro-p-toluidine (hereafter referred to as Unnamed). Rate of degradation was directly correlated with temperature and moisture content. First order kinetics adequately described the rate of degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 14 publications
6
34
1
Order By: Relevance
“…Similarly, Barrett and Lavy (1983) reported rapid pendimethalin dissipation during the first 14 d after application. The initial rapid dissipation of other soil applied dinitroanilines has been previously reported (Poku and Zimdahl 1980;Serrano et al 2010;Zimdahl and Gwynn 1977). The rapidly dissipated fraction of pendimethalin does not contribute greatly to weed control; therefore, it is the second phase of dissipation that is important for weed management (Shaner 2012).…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, Barrett and Lavy (1983) reported rapid pendimethalin dissipation during the first 14 d after application. The initial rapid dissipation of other soil applied dinitroanilines has been previously reported (Poku and Zimdahl 1980;Serrano et al 2010;Zimdahl and Gwynn 1977). The rapidly dissipated fraction of pendimethalin does not contribute greatly to weed control; therefore, it is the second phase of dissipation that is important for weed management (Shaner 2012).…”
Section: Resultsmentioning
confidence: 77%
“…Turfgrass thatch is a tightly intermingled layer of living and dead stems, leaves and roots of grass that develops between vegetation and the soil surface (Beard, 1973 The final detection of trifluralin and benfluralin has been made with ECD (Tepe and Scroggs, 1967, Zimdahl and Gwynn, 1977, Day, 1978 T I ' It has been demonstrated before Niemczyk, 1990a, 1990) that solid-phase extraction/purif- …”
Section: Resultsmentioning
confidence: 99%
“…The existing residue methodologies (Tepe and Scroggs, 1967, zimdahl and Gwynn, 1977, Day, 1978 The technique presented in this paper combines the use of solid-phase extraction/purification and megabore, fused silica column gas chromatography with NP detection for either simultaneous or separate analysis of trifluralin and benfluralin residues in turfgrass thatch and soil. …”
Section: Introductionmentioning
confidence: 99%
“…The direct relationship between soil Downloaded by [Erciyes University] at 14:14 27 December 2014 temperature and degradation is well established (Zimdahl and Gwynn, 1977;Zimdahl and Clark, 1982;Ismail and Teoh, 1994). We also found that the degradation rate of pretilachlor was the highest at 35 C C for the three soil types studied.…”
Section: Discussionmentioning
confidence: 99%